The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13643-020-01550-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for the prevention of type 2 diabetes mellitus in low and middle-income countries: protocol for a systematic review and meta-analysis of randomized controlled trials

Abstract: Introduction The disease burden caused by type 2 diabetes mellitus is a prime public health concern. The prevalence and rate of deaths from diabetes mellitus in low- and middle-income countries (LMICs) are higher than the high-income countries. Increased physical activity and a balanced diet are essential and successful measures to prevent the onset of diabetes mellitus. This systematic review aims to explore the available non-pharmacological approaches for the prevention of type 2 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The systematic review is registered in the International Prospective Register of Systematic Reviews. The protocol outlines the approach in depth, including the development of the search strategy, double-screening, double-data extraction, double-quality assessment of included articles and narrative synthesis 27. A detailed search strategy (online supplemental table 1) was constructed using the keywords including Exercise, ‘Physical activity’, ‘Nutritional therapy’’, ‘Meal plan’, ‘Weight loss’, ‘Lifestyle change’, ‘Lifestyle modification’, Diabetes, ‘Diabetes mellitus’, ‘Type 2 diabetes mellitus’’, T2DM, DM, LMICs, ‘Developing country’, ‘Peri-urban’’, urban, rural to search different electronic bibliographic database including MEDLINE through PubMed, Embase, the Cochrane Library (Cochrane Central Register of Controlled Trials-CENTRAL), Web of Science, ClinicalTrials.gov, International Clinical Trials Registry Platform, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The systematic review is registered in the International Prospective Register of Systematic Reviews. The protocol outlines the approach in depth, including the development of the search strategy, double-screening, double-data extraction, double-quality assessment of included articles and narrative synthesis 27. A detailed search strategy (online supplemental table 1) was constructed using the keywords including Exercise, ‘Physical activity’, ‘Nutritional therapy’’, ‘Meal plan’, ‘Weight loss’, ‘Lifestyle change’, ‘Lifestyle modification’, Diabetes, ‘Diabetes mellitus’, ‘Type 2 diabetes mellitus’’, T2DM, DM, LMICs, ‘Developing country’, ‘Peri-urban’’, urban, rural to search different electronic bibliographic database including MEDLINE through PubMed, Embase, the Cochrane Library (Cochrane Central Register of Controlled Trials-CENTRAL), Web of Science, ClinicalTrials.gov, International Clinical Trials Registry Platform, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Each kilogram of weight loss results in a 16% relative risk reduction and strongly correlates with a decreased progression to Type 2 diabetes. 14 According to a clinical investigation carried out in Da Qing, China, diet or exercise or a combination of diet and exercise was significantly linked to reductions in the probability of acquiring diabetes by 31%, 46%, and 42%, respectively. 15 People with a higher likelihood of developing diabetes should undergo more frequent screenings.…”
Section: Tackling Strategiesmentioning
confidence: 99%
“…Consequently, it is possible that preventive measures may preclude T2D development. Accumulating evidence has demonstrated that early impaired insulin sensitivity and prediabetes can be addressed by nonpharmacological measures [62,71,72]. The latter may include reducing carbohydrate intake and increasing intake of healthy fats in combination with an anti-inflammatory diet (a dietary approach that emphasizes the consumption of foods with anti-inflammatory properties while minimizing or avoiding foods that can promote inflammation) to reduce systemic inflammation [73].…”
Section: Potential Nonpharmacological Approachesmentioning
confidence: 99%
“…The latter may include reducing carbohydrate intake and increasing intake of healthy fats in combination with an anti-inflammatory diet (a dietary approach that emphasizes the consumption of foods with anti-inflammatory properties while minimizing or avoiding foods that can promote inflammation) to reduce systemic inflammation [73]. Furthermore, enhanced physical activity and exercise, especially exercises which build skeletal muscle (i.e., weight lifting, burst training, or high-intensity interval training), as well as effective management of psychological stress, can improve insulin sensitivity [62,71,72]. Given that antipsychotic agents are essential in treating schizophrenia, and that the risk of prediabetes and T2D rapidly increases following the initiation of antipsychotic treatment, nonpharmacological measures may be clinically beneficial.…”
Section: Potential Nonpharmacological Approachesmentioning
confidence: 99%